ANALYSIS OF THE QUALITY OF SOUNDING DATA IN RELATION TO THE DIFFERENCES IN SEABED TOPOGRAPHY - Lestari , Ria Putri; Pratomo , Danar Guruh; Setiyadi, Johar (Geoid, 2009)
Visualizations of seabed surface topography is obtained from such an activity called sounding survey. Points of measurement of the depth are located sounding line and checkline crossing. In the research analysis is carried out on the relationship between the quality of the sounding data and the topography of the seabed, which was divided into five (5) criteria, that is, coral (Cr), coral sand (CrS), mud (M), mud sand (MS), and sand (S).In order to know the sounding data quality, is done by comparing the depth of intersection of the sounding line and the checkline crossing which is then referred to as the analysis point. The position and the depth of this point is found by the linear intepolation method. The result of this research indicate that there are irregularities in the depth of the analysis point, which indicates an error in the measurement accuracy. If viewed from the mistake that occur in the analysis point, the analysis points of the depth profile with the seabed topography of mud sand (MS) has the best accuracy compared to the other profiles. While the analysis poinst in the depth profile of coral (Cr) has the least level of accuracy compared to the others. Thus it can be said that the depth measurement done on mud sand (MS) has the best quality and the depth measurement done on coral (Cr) has the lowest quality.